Effect of hemostatic agent on microshear bond strength of total-etch and self-etch adhesive systems - Hoorizad, Maryam (Dent Res J (Isfahan), 2019)
BACKGROUND: Application of hemostatic agents can negatively affect the bond strength of adhesive systems to dental substrate. This study aimed to assess the effect of ferric sulfate on microshear bond strength of four total- and self-etch adhesives to dentin after water storage. MATERIALS AND METHODS: In this in vitro study, 192 dentin slices with 2 mm thickness were made of 64 extracted sound human third molars. The samples were divided into 8 groups (n = 24) as follows: G1: Scotchbond Multi-Purpose, G2: hemostatic agent + Scotchbond, G3: Adper Single Bond, G4: hemostatic agent + Adper, G5: Clearfil SE Bond, G6: hemostatic agent + Clearfil, G7: Single Bond Universal, and G8: hemostatic agent + Single Bond Universal. Composite cylinders with 0.7 mm diameter and 1 mm height were bonded to the surfaces. Each group was then divided into two subgroups (n = 12) for water storage for 24 h and 3 months. The microshear bond strength was then measured. Data were analyzed using the Shapiro–Wilk test, three-way ANOVA, one-way ANOVA, and Tukey's test (P < 0.05). RESULTS: Application of ferric sulfate decreased the bond strength of all bonding agents after both 24 h and 3 months of storage; but, this reduction was not statistically significant (P > 0.05). Single Bond Universal at 24 h showed the highest and Adper Single Bond at 3 months showed the lowest bond strength (P < 0.001). CONCLUSION: Dentin contamination with hemostatic agents negatively affects the bond strength of total- and self-etch adhesives.